The first annotated checklist of parasites infecting the one-humped camel, Camelus dromedarius (Artiodactyla: Camelidae), of Saudi Arabia between 1950-2021 - Alnaqeb, Haitham (Journal of Parasite Science, 2024)
Based on the published works of camels in Saudi Arabia, this study is the first checklist of parasites infecting the one-humped camel, Camelus dromedarius in Saudi Arabia between 1950-2021. The present checklist was organized taxonomically in which consist of 75 names representing 4 groups of parasites. The first group is Protozoa with 24 names. Secondly, 13 names of nematodes were reported while there were 12 names of Platyhelminthes. The last group belongs to the Arthropoda which consists of 26 reported species, most of which belong to Ixodida. Based on the resulting checklist, the geographical sampling of these records focuses mainly on the Central, Western, Eastern, and Southern regions, respectively. To date, a few studies have recorded parasites in the North region. The evidence reviewed in this list seems to suggest that further research should be undertaken to investigate the biodiversity of parasites infecting camels from the northern region of Saudi Arabia, which is connected to other continents of Asia, Africa, and Europe.